Advances in Mesenchymal stem cells regulating macrophage polarization and treatment of sepsis-induced liver injury - Chen, Yuhao; Yang, Lihong; Li, Xihong (Frontiers in Immunology, 2023)
Sepsis is a syndrome of dysregulated host response caused by infection, which leads to life-threatening organ dysfunction. It is a familiar reason of death in critically ill patients. Liver injury frequently occurs in septic patients, yet the development of targeted and effective treatment strategies remains a pressing challenge. Macrophages are essential parts of immunity system. M1 macrophages drive inflammation, whereas M2 macrophages possess anti-inflammatory properties and contribute to tissue repair processes. Mesenchymal stem cells (MSCs), known for their remarkable attributes including homing capabilities, immunomodulation, anti-inflammatory effects, and tissue regeneration potential, hold promise in enhancing the prognosis of sepsisinduced liver injury by harmonizing the delicate balance of M1/M2 macrophage polarization. This review discusses the mechanisms by which MSCs regulate macrophage polarization, alongside the signaling pathways involved, providing an idea for innovative directions in the treatment of sepsis-induced liver injury.